Systematic review and meta-analysis of genetic studies of late-life depression. (April 2017) - Tsang, Ruby S.M.; Mather, Karen A.; Sachdev, Perminder S.; Reppermund, Simone
Highlights: A systematic review and meta-analysis of genetic studies of LLD were conducted. The review included 46 candidate gene studies and one GWAS. Meta-analysis revealed APOE, BDNF, and SLC6A4 being associated with risk of LLD. One genome-wide significant signal in the 5q21 region was detected in the GWAS. Abnormal hippocampal plasticity and stress reactivity are implicated in LLD etiology. Abstract: Late-life depression (LLD) is thought to be multifactorial in etiology, including a significant genetic component. While a number of candidate gene studies have been carried out, results remain inconclusive. We undertook a systematic review of all genetic association studies of depression or depressive symptoms in late life published before February 2016, and performed meta-analyses on polymorphisms investigated in three or more independent studies. A total of 46 candidate gene studies examining 56 polymorphisms in 23 genes as well as a genome-wide association study (GWAS) were included. Meta-analyses were conducted for four polymorphisms using random effects models, of which three ( APOE, BDNF, SLC6A4 ) were associated with LLD. These genes are implicated in hippocampal plasticity and stress reactivity, suggesting that dysregulation of these pathways may contribute to LLD. Despite using a large sample, the only GWAS published to date identified only one genome-wide significant locus in the 5q21 region. In the future, larger genetic studies specifically examining LLD, including non-hypothesis-driven GWAS, are required to further identify genetic determinants of LLD.